The Application Of Servqual Method and Importance Performance Analysis (IPA) in Analyzing The level of Patient Satisfaction With the Quality of Service at Wira Husada Kisaran General Hospital - Sirait, Naomi Natasya; Marbun, James Piter (JMEA : Journal of Mathematics Education and Application, 2023)
One of the health care facilities are hospital. Hospitals are required to provide quality services to give satisfaction to the patient. Services that are less than optimal will reduce the number of patients visiting. Therefore, improving the quality of service is needed in an effort to attract patients to seek treatment at the WiraHusadaKisaran General Hospital. This research was conducted by distributing 70 questionnaires and calculations were carried out using the Importance Performance Analysis (IPA) method and the Servqual method. The Servqual method is used to determine the level of patient satisfaction and the Importance Performance Analysis (IPA) method is used to determine which attributes need improvement. From the results of the calculation of the Servqual method using 5 dimensions of service, namely tangible, reliability, responsiveness, assurance, and empathy to determine the value of GAP. On the tangible dimensions of the attributes that have not satisfied the patient, the comfort and cleanliness of the hospital and inpatient environment. In the dimension of reliability attributes that have not satisfied the patient, the doctor conducts an examination of the patient according to the specified schedule and on time. In the dimension of responsiveness attributes that have not satisfied patients, namely, nurses quickly and responsively serve patients. On the assurance dimension has satisfied patients. In the dimension of emphaty attributes that have not satisfied the patient, namely, medical personnel respond to patient complaints. From the results of the calculation of the Importance Performance Analysis (IPA) method, it has a suitability level value of 79.34% and in the Cartesian diagram of the 20 attributes there are 6 attributes that require repair and improvement, namely attribute numbers 1, 3, 4, 8, 9, and 12.